Toxicity assessment and analgesic activity investigation of aqueous acetone extracts of Sida acuta Burn f . and Sida cordifolia L. (Malvaceae), medicinal plants of Burkina Faso - Konaté Kiessoun; Bassolé Imaël Henri; Hilou Adama; Aworet-Samseny Raïssa RR; Souza Alain; Barro Nicolas; Dicko Mamoudou H; Datté Jacques Y; M'Batchi Bertrand (BMC, 2012)
Abstract Background Sida acuta Burn f. and Sida cordifolia L. (Malvaceae) are traditionally used in Burkina Faso to treat several ailments, mainly pains, including abdominal infections and associated diseases. Despite the extensive use of these plants in traditional health care, literature provides little information regarding their toxicity and the pharmacology. This work was therefore designed to investigate the toxicological effects of aqueous acetone extracts of Sida acuta Burn f. and Sida cordifolia L. Furthermore, their analgesic capacity was assessed, in order to assess the efficiency of the traditional use of these two medicinal plants from Burkina Faso. Method For acute toxicity test, mice were injected different doses of each extract by intraperitoneal route and the LD50 values were determined. For the subchronic toxicity evaluation, Wistar albinos rats were treated by gavage during 28 days at different doses of aqueous acetone extracts and then haematological and biochemical parameters were determined. The analgesic effect was evaluated in mice by the acetic-acid writhing test and by the formalin test. Results For the acute toxicity test, the LD50 values of 3.2 g/kg and 3.4 g/kg respectively for S. acuta Burn f. and S. cordifolia L. were obtained. Concerning the haematological and biochemical parameters, data varied widely (increase or decrease) according to dose of extracts and weight of rats and did not show clinical correlations. The extracts have produced significant analgesic effects by the acetic acid writhing test and by the hot plate method (p <0.05) and a dose-dependent inhibition was observed. Conclusion The overall results of this study may justify the traditional uses of S. acuta and S. cordifolia .